Provoquer des archives et invoquer la mémoire - Marys Renné Hertiman (Glad!)
The presumed absence of female comic strip creators in the history of this medium is due, in part, to the lack of sources that could lead to the restitution of their traces. In this context, a group of women researchers, calling themselves Les Bréchoises, have joined forces to create archives of women in the French ninth art and thus to constitute desired monuments, monuments of memory. This ambitious research project reflects an ambivalent posture: scientific and militant at the same time. Starting from the presupposed non-existence of the comic book heritage and the unveiling of the backstage of a project of memorialization, this article returns to the components of the organic practice of the archive.